Exploring research and scholarship at Historically Black Colleges and Universities: insights from federal funding patterns and investigator experiences - Akter, Sayema; Hucek, Freda Allyson; McCollum, Quentin; Levkoff, Sue E.; Friedman, Daniela B. (Frontiers in Education, 2025)
IntroductionHistorically Black Colleges and Universities have played a key role in advancing educational equity and remain essential in shaping a more inclusive and diverse research landscape. However, persistent structural barriers limit their full participation in national research priorities. There remains limited comprehensive awareness of the unique barriers and opportunities encountered by investigators within HBCUs. This study explores the experiences of investigators at HBCUs, examining the challenges and opportunities they encounter in conducting research.MethodA two-phased exploratory approach was utilized, including a qualitative content analysis of grant entries from the National Institutes of Health (NIH) and National Science Foundation (NSF) and an online survey of HBCU investigators between February 7th and April 10th, 2024.ResultsThe content analysis highlights HBCU faculty’s strong contributions to research areas of science, technology, engineering, mathematics (STEM), advanced technology and data science, environmental sciences, and health. The survey findings reveal challenges related to funding, research infrastructure, and a lack of targeted support for enhancing faculty research capabilities. Participants also highlighted several challenges, including administrative burdens, under-resourced support for research and activities, lack of funding, and the need for policy changes. Results suggest the pressing need for HBCUs to address workload balance, improve mentorship, provide professional support for grant submission, and reduce administrative burdens to increase the research productivity of investigators.DiscussionFindings reinforce a strategic role in advocating equitable research policies and institutional support structures at HBCUs. Effective central leadership and sustained institutional support are essential for HBCUs to address these challenges. These efforts are not merely a measure of faculty productivity; they also contribute to broader national goals by enhancing the future research environment and promoting inclusive excellence in higher education, particularly for underrepresented institutions.